Night film ebook A novel. - Pessl, Marisha (2013)
NEW YORK TIMES BESTSELLER • “A hair-raising mystery that’s equal parts family drama, horror movie, and jigsaw puzzle. . . . It’s impossible to look away.”— People (four stars) “Maniacally clever . . . like an M.C. Escher nightmare about Edgar Allan Poe . . . You’ll miss your subway stop, let dinner burn, and start sleeping with the lights on.”— The Washington Post   A BEST BOOK OF THE YEAR: NPR, Cosmopolitan, Kirkus Reviews, BookPage   On a damp October night, beautiful young Ashley Cordova is found dead in an abandoned warehouse in lower Manhattan. Though her death is ruled a suicide, veteran investigative journalist Scott McGrath suspects otherwise. As he probes the strange circumstances surrounding Ashley’s life and death, McGrath comes face-to-face with the legacy of her father: the legendary, reclusive cult-horror-film director Stanislas Cordova—a man who hasn’t been seen in public for more than thirty years.   For McGrath, another death connected to this seemingly cursed family dynasty seems more than just a coincidence. Though much has been written about Cordova’s dark and unsettling films, very little is known about the man himself. Driven by revenge, curiosity, and a need for the truth, McGrath, with the aid of two strangers, is drawn deeper and deeper into Cordova’s eerie, hypnotic world.   The last time he got close to exposing the director, McGrath lost his marriage and his career. This time, he might lose even more.